Effect of Locally Made Riser Type and Operating Pressures of the Fixed Sprinkler Irrigation System (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
A field experiment was conducted during growing season of 2021, to evaluate the effect of the types of locally made riser and the operating pressures of the fixed sprinkler irrigation system on some soil characteristics and the production of maize crop at Al-Raed Research Station located in the Akkarouf area on the Abu Ghraib-Shoala